2009
DOI: 10.1111/j.1548-1352.2009.01054.x
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Psychiatric and Anthropological Approaches: The Case of “Nerves” in the United States

Abstract: Psychiatrists and anthropologists have taken distinct analytic approaches when confronted with differences between emic and etic models for distress: psychiatrists have translated folk models into diagnostic categories whereas anthropologists have emphasized culture-specific meanings of illness. The rift between psychiatric and anthropological research keeps "individual disease" and "culture" disconnected and thus hinders the study of interrelationships between mental health and culture. In this article we bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…For instance, the question of duration remains (i.e., does tension refer to a passing feeling or a more long-term state?). Similar nonspecific categories such as ''nerves'' have been noted in U.S. populations (Dahlberg et al 2009); a cross-cultural comparison that considers ''tension'' not as an expression for a psychiatric condition but as a distinct category could be a fruitful future direction and is, in any case, an important step toward generating a locally derived understanding of mental health and illness.…”
Section: Discussionmentioning
confidence: 72%
“…For instance, the question of duration remains (i.e., does tension refer to a passing feeling or a more long-term state?). Similar nonspecific categories such as ''nerves'' have been noted in U.S. populations (Dahlberg et al 2009); a cross-cultural comparison that considers ''tension'' not as an expression for a psychiatric condition but as a distinct category could be a fruitful future direction and is, in any case, an important step toward generating a locally derived understanding of mental health and illness.…”
Section: Discussionmentioning
confidence: 72%
“…'Nervios' has been frequently described among Mexicans and other Hispanic countries [28,32]. The study of 'nervios' is extensive, and it has been suggested that it is a syndrome of chronic dysphoric mood with somatic complaints [33] whose origins are rooted in social problems [34]. Independently of the exact definitions, for some Peruvians older adults, 'nervios' were perceived as something that can be mitigated with anxiolytics.…”
Section: Discussionmentioning
confidence: 99%
“…'Nervios' has been frequently described among Mexicans and other Hispanic countries (28,32). The study of 'nervios' is extensive, and it has been suggested that it is a syndrome of chronic dysphoric mood with somatic complaints (33) whose origins are rooted in social problems (34). Independently of the exact de nitions, for some Peruvians older adults, 'nervios' were perceived as something that can be mitigated with anxiolytics.…”
Section: Discussionmentioning
confidence: 99%